A new species of Cichlidogyrus Paperna, 1960 (Platyhelminthes: Monogenea: Dactylogyridae) infecting tilapias in Lake Kariba (Zimbabwe), with a discussion on its phylogenetic position. Issue 1 (31st December 2022) - Geraerts, Mare; Huyse, Tine; Vanhove, Maarten P. M.; Artois, Tom
Abstract : Monogeneans dominate the external parasite fauna of bony fish. During recent years, examination of more populations and species of Cichlidogyrus Paperna, 1960 has led to the (re)description of several species. Cichlidogyrus halli (Price & Kirk, 1967 ) Price, 1968, for example, has been redescribed several times in the past and has been proposed to encompass many (pseudo)cryptic species. In Lake Kariba (Zimbabwe), specimens of a species of Cichlidogyrus were found that morphologically resemble C. halli . These specimens were found on the gills of native Oreochromis cf. mortimeri and Coptodon rendalli (Boulenger, 1897), and introduced Nile tilapia Oreochromis niloticus (Linnaeus, 1758). A detailed study of the morphology of these specimens, including morphometrics, and a thorough comparison with specimens of C. halli is presented. Part of the COI gene and 18S-ITS1 fragment were sequenced and analysed to provide insight into the phylogenetic placement of these specimens within the Cichlidogyrus–Scutogyrus monophylum. We found that C. halli and the new specimens sp. nov. are sister clades within the same monophyletic clade, and that clear morphological and morphometric differences are present in the dorsal bar of the haptor (auricles almost twice as long as in C. halli ) and the male copulatory organ (wider penis stylet, longer accessory piece with a more elongated and less pronounced terminal triangular cap, narrower heel, as compared with C. halli ). Based on these results, the new specimens are described as a new species: C. chloeae sp. nov. The role of introduced Nile tilapia as a potential reservoir for native parasites raises concern for potential spillbacks and stresses the need for further monitoring of monogeneans on native and introduced tilapias. http://zoobank.org/urn:lsid:zoobank.org:pub:DAF7DD13-6A31-4271-970B-A03DEEDD3938